2017
DOI: 10.1589/jpts.29.1001
|View full text |Cite
|
Sign up to set email alerts
|

Does the weakening of intrinsic foot muscles cause the decrease of medial longitudinal arch height?

Abstract: [Purpose] There are no reliable evidences that the weakening of intrinsic foot muscles causes the decrease of the medial longitudinal arch (MLA) height. The purpose of this study was to confirm whether the fatigue of intrinsic foot muscles decrease the MLA height during standing and gait using 3D motion analysis system. [Subjects and Methods] Twenty healthy male subjects participated in this study. Foot kinematics was measured using an Oxford Foot Model before and after fatigue-inducing exercises of the abduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Doming has been proposed as a rehabilitation exercise to strengthen intrinsic foot muscles, in part because it engages the AH more than toe flexion does (ref 23 here too). However, the extrinsic TA and TP muscles can overpower or overcompensate for weak intrinsic muscles [28], causing an existing muscle imbalance to persist even after doming training. Future studies should focus on training strategies that isolate the AH from the TA and TP.…”
Section: Discussionmentioning
confidence: 99%
“…Doming has been proposed as a rehabilitation exercise to strengthen intrinsic foot muscles, in part because it engages the AH more than toe flexion does (ref 23 here too). However, the extrinsic TA and TP muscles can overpower or overcompensate for weak intrinsic muscles [28], causing an existing muscle imbalance to persist even after doming training. Future studies should focus on training strategies that isolate the AH from the TA and TP.…”
Section: Discussionmentioning
confidence: 99%
“…We can mention the toe flexor strength with toe-dynamometry (Spink et al, 2010 ) and the paper grip test (De Win et al, 2002 ) and there are several indirect tests assessing the strength or stiffness through the deformation or mobility of the foot arches in weight bearing and non-weight bearing conditions. They are the medial arch height (Okamura et al, 2017 ), the arch rigidity index (Mulligan and Cook, 2013 ), the navicular drop (ND), and the foot mobility measurement (FMM) (McPoil et al, 2009 ), which we will describe in detail.…”
Section: Testing Foot Strengthmentioning
confidence: 99%
“…This assessment performed during gait and/or standing phase requires the use of the Oxford Foot Model, a 3D multi-segment foot model with a good to excellent repeatability (Okamura et al, 2017 ). In this test, the MLA height is defined as the normal distance of the plane of the forefoot from the proximal first metatarsal marker by the Oxford Foot Model.…”
Section: Testing Foot Strengthmentioning
confidence: 99%
“…Further evidence for this direct anatomical link stems from previous studies in cadaver feet and living young adults [36,42]. These studies showed that, when the foot is fully on the ground and loaded with body weight, foot segment positions are almost constant [42] but PA strain gradually increases with increases in Achilles tendon forces until push-off [36]. We computed therefore total PA strain as the sum of kinematic changes (MTP dorsiflexion angles and calcaneus movement) and increases in Achilles tendon forces.…”
Section: Limitationsmentioning
confidence: 95%
“…The PA is anatomically connected to the paratenon of the Achilles tendon through the periosteum of the heel [12]. Further evidence for this direct anatomical link stems from previous studies in cadaver feet and living young adults [36,42]. These studies showed that, when the foot is fully on the ground and loaded with body weight, foot segment positions are almost constant [42] but PA strain gradually increases with increases in Achilles tendon forces until push-off [36].…”
Section: Limitationsmentioning
confidence: 99%